Empowering Wana Kriya MSMEs Through Utilizing Local Wood Into Decoration and Accessory Products - LESTARI, Ni Putu Emilika Budi; PRANAJAYA, I Kadek; PUTRI, Putu Yudha Asteria; DEWI, Ni Made Emmi Nutrisia; PRASIANI, Ni Komang; MANDALA, I Gusti Ngurah Agung Kepakisan; MAHADIPTA, Ngurah Gede Dwi; PARAMITA, Ni Kadek Ayu Pradnya; WICAKSANA, Gede Dharma Arya; CAHYONO, Irfan; WIRATAMA, Dhanendra; WIBAWA, Ida Bagus Surya (PT Keberlanjutan Strategis Indonesia, 2025)
This community service program aims to empower the Wana Kriya MSME in Pering Village, Gianyar, Bali through the sustainable use of local wood to create economically valuable decorative and accessory products. The activities are carried out through several stages, including socialization, training in creativity and product design innovation, branding training, photography, product identity, and visual content. In addition, training is provided on digital marketing and social media utilization, MSME management, production, and entrepreneurship. The counseling and community empowerment program is carried out with the theme